TEACHERS AND LEARNERS PERCEPTION: CASE STUDIES WITH CLIL FOR MILITARY UNDERGRADUATES - Enock Amalanathan (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
This paper is a preliminary report on the teachers’ and learners’ perception on case studies with CLIL program carried out during an EAP course in the National Defense University of Malaysia (NUDM). Content and Language Integrated Learning (CLIL) is relatively very little known in the military context. However recently researches have revealed that CLIL is becoming popular and widespread in many universities. Based on CLIL benefits and dual-focus approach, teachers and curriculum developers have adapted accordingly to their course objectives and requirements. On the other hand, the case study method is an active teaching and learning method which provides rich contextual information and opportunities for language learners to develop more possible ways to learn and use the language creatively and practically in various language situations. This paper discusses preliminary findings of an EAP course for undergraduates in NDUM where the case study method and Content and Language integrated Learning is collaborated. A total of 84 military cadets and 3 teachers from an EAP program participated in the study. The questionnaire items were structured for the students and semi-structured interviews were designed for the teachers. The overall results projected the students’ and teachers’ positive views about case study and CLIL pedagogy that contributed towards language achievement. The paper concludes with discussion highlighting key issues that remain to be addressed and outline direction for future research.